FAKTOR-FAKTOR PENDORONG DAN PENARIK WISATAWAN BERKUNJUNG KE OBJEK WISATA GUNUNG DEMPO - Sumarni Sumarni; Zulkarnain Zulkarnain; I Gede Sugiyanta (JPG (Jurnal Penelitian Geografi), 2013)
The objectives of this research were find out the information about the factors that motivates and attracted the tourist to visit the Dempo mountain object place in south Pagar Alam district of Pagar Alam city of south Sumatera province in 2011. The point of this investigation in this research were to escape from the saturation, refreshing of the body (relaxation), searching the entertainment/game, romantic atmosphere, beautiful place, climate condition, accessibility and facility.   The method that was used in this research was descriptive explorative method. The population in this research was the tourists who come to the Dempo mountain object place. The researcher took the sample were 60 respondents and the selected of the sample accidental sampling technique.  In collecting the data the researcher used observation, documentation, and structure interview. In analyzing the data, the researcher used percentage analysis.  Based on the result data ananysis it can be concluded that: There are 49 respondents who stated that they want to escape from the saturation was the factor that motivates them to visit Dempo mountain object place. There are 47 respondents or 78 % stated that they come to the object place for the reason to refresh the body (relaxation). There are 34 respondents or 57% stated that they want to come to the Dempo mountain object place for the reason to play the game. There are 36 respondents stated that for the reason to find the romantic atmosphere was the factor that motivates the tourist to visit Dempo mountain object place. There are 57 respondents or 95% stated that the factor that attracted the tourist to visit the Dempo mountain object place because of the beautiful of nature. There are 55 respondents or 92% stated that that the factor that attracted the tourist to visit the Dempo Mountain object place because the climate condition.  There are 44 respondents or 73% stated that because of the easy of the accessibility was the factor that attracted the tourist to visit the Dempo mountain object place. And there are 46 respondents or 77%) stated that the complete enough facility was the factor that attracted the tourist to visit the Dempo mountain object place. Key wodrs: the factors that motivates and attracted